THE EFFECT OF ASH AND ASH CONSTITUENTS ON THE LIQUEFACTION YIELD OF TURKISH LIGNITES AND ASPHALTITES - ONER, M; ONER, G; BOLAT, E; YALIN, G; KAVLAK, C; DINCER, S (BUTTERWORTH-HEINEMANN LTD, 1994)
The objective of this work was to study mineral matter effects in coal liquefaction. A suite of 16 lignites and two asphaltites have been liquefied in a batch autoclave under a standard set of reaction conditions. Experiments were performed at 440-degrees-C, 60 min residence time and 8 MPa hydrogen pressure (cold charge). All experiments were carried out in solvents, like anthracene oil, creosote oil, tetralin and TUPRAS vaccum residual oil, at a solvent:lignite ratio of two. The ash content of lignites and asphaltites ranged from 7.73 (dry) to 59.99% (dry). It was found that, generally, as the ash content increased, the total conversion of lignite and conversion to tetrahydrofuran (THF), toluene or hexane solubles increased; total conversion, THF and toluene solubles yields appear to remain constant at high ash contents. Multiple regression analysis was employed to relate yield and conversion data with specific ash minerals.
Keywords: ASH; LIQUEFACTION YIELD; EFFECT; COAL-LIQUEFACTION; BEHAVIOR; DEPENDENCE; HYDROLIQUEFACTION; HYDROGENATION; Energy & Fuels; Engineering